Language Skills and Thinking in Children Aged 6‒10 Years. Research Report - Sage, Rosemary J.W.B; Sage, Luke D. (Przegląd Psychologiczny, 2024)
Aim: Language and thinking play a key role in human interactions. Their quality is deteriorating as conversations are replaced by technology (Sage, 2020). This, in turn, raises problems in communication and relationship building, reduces work efficiency and contributes to a decline in personal and professional standards. The aim of the research presented here was to determine how thinking and expressive language skills are formed in school-aged children in the East Midlands region of England and to see if these abilities improved after a year of study. Method: 102 children aged 6‒10 took part in the study, which involved four tasks: two pictorial and two involving story-telling. Structured in this way, the study was designed to stimulate thinking and linguistic expression and to elicit narratives, reflecting the generation of ideas in response to visual and auditory stimuli. The study was conducted in two stages: a group of children was first examined in 2022, and the study was repeated in 2023. The t statistic for dependent samples was used to assess the significance of differences. Results: Significant differences were found, indicating improvements in narrative skills with the introduction of story-telling activities. In contrast, language and thinking skills remained stable but low. Conclusions: Retest revealed a lack of significant differences between means of thinking ability and linguistic expressions. After a year of working with students, the level of their imagination and thinking flexibility has not improved. These abilities are crucial to the development of creative thinking and imagination and, consequently, to the overall development and success of the individual. On the other hand, there was an improvement in narrative competence, which is an important part of developing social interaction.